Organizing degrowth: The ontological politics of enacting degrowth in OMS. (May 2021) - Vandeventer, James Scott; Lloveras, Javier
As degrowth notions begin to gain traction within business schools and organization and management studies (OMS), this paper draws on Science and Technology Studies to interrogate the ontological politics of enacting degrowth in this relatively new context. We argue that the 'degrowth multiple' is a boundary object which takes on different forms as it circulates among different epistemic communities and within their respective boundaries, institutional arrangements, practices, and agendas. We investigate this empirically to elucidate how degrowth is being enacted within the OMS epistemic apparatus, revealing three sets of practices characterizing extant OMS-degrowth engagements: stabilizations, reconfigurations, and projections . These motivate a subsequent discussion of the ontological politics unfolding through degrowth performances in OMS, its transformations (t)herein, and degrowth's wider enrollment within the OMS epistemic apparatus. We thus contribute a reflexive intervention to organizing degrowth such that it remains a politically actionable concept across multiple contexts, and avoids becoming uncritically black-boxed, fetishized, and/or diluted by diverging cross-boundary enactments.